2020
DOI: 10.3390/ijms21176407
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological Expression of SOX-10 in Triple-Negative Breast Cancer: A Descriptive Analysis of 113 Samples

Abstract: Background: SRY-related HMG-box 10 (SOX-10) is commonly expressed in triple negative breast cancer (TNBC). However, data on the biological significance of SOX-10 expression is limited. Therefore, we investigated immunhistological SOX-10 expression in TNBC and correlated the results with genetic alterations and clinical data. Methods: A tissue microarray including 113 TNBC cases was stained by SOX-10. Immunohistological data of AR, BCL2, CD117, p53 and Vimentin was available from a previous study. Semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…SOX10 expression may lead to confusion in diagnosis but many studies have proven that breast carcinomas, particularly basal-like, triple-negative phenotypes, are also labeled by SOX10 [19]. This study is the continuation of a similar study conducted by Katharina et al in Germany [20].…”
Section: Discussionmentioning
confidence: 54%
“…SOX10 expression may lead to confusion in diagnosis but many studies have proven that breast carcinomas, particularly basal-like, triple-negative phenotypes, are also labeled by SOX10 [19]. This study is the continuation of a similar study conducted by Katharina et al in Germany [20].…”
Section: Discussionmentioning
confidence: 54%
“…While others have found greater sensitivities using GATA3, this study demonstrated mammaglobin's increased ability to identify non-luminal tumors from 23% to 48%, which is much higher than previously reported by Liu et al [30] (35% of ER negative tumors), Ordonez and Sahin [31] (18% of TNBCs), and Krings et al [31] (26% of TNBCs). Still, given that either GATA3 or mammaglobin fail to identify more than 50% of TNBCs these markers should be supplemented with markers speci c for TNBC, such as Sry-related HMG box (SOX) 10, which is found in 40%-70% of TNBCs and appears to be expressed in tumors that are negative for GATA3 [32][33][34]. More recently, it was demonstrated that adding SOX10 improved the sensitivity of the markers in metastatic breast cancer (sensitivity = 0.89), metastatic TNBC (0.78), and primary TNBC (0.78) [35].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, SOX-10 may be helpful. 28 Primary small cell carcinoma of the breast is extremely rare. The negative expression of ER and PR in the small cell carcinoma favors metastasis since the very rare examples of primary small cell carcinoma of the breast express these markers in 33% to 50% of cases.…”
Section: Discussionmentioning
confidence: 99%